Concentration- and time-dependent behavioural effects of ethanol on Lumbriculus variegatus - Aidan Seeley (Genes, Brain and Behavior, 2024)
Ethanol is one of the most widely used drugs in the world. Ethanol induces profound physiological and behavioural responses in invertebrate model organisms, such as Caenorhabditis elegans and Drosophila melanogaster. Lumbriculus variegatus (Annelida, Oligochaete) is an aquatic worm which shows behavioural responses to common drugs and thus is potentially useful in pharmacological research. The effects of ethanol are unknown in this organism. In this study, we examine the effects of acute exposure to ethanol (0-500 mM) on the stereotypical movements and locomotor activity of L. variegatus and examine the concentration- (0-500 mM) and time-dependent (0-210 min) effects of ethanol in L. variegatus. We show that ≥250 mM ethanol reversibly reduced the ability of tactile stimulation to elicit stereotypical movements, namely body reversal and helical swimming and locomotor activity (p < 0.05, N = 8). We also found that 2 min of exposure to ≥250 mM ethanol rapidly induces steady-state hypokinesis (p < 0.05, N = 11) and confirm ethanol absorption into L. variegatus tissues. Additionally, we also observed acute ethanol tolerance after 150 min of exposure to 500 mM ethanol (p < 0.05, N = 24). This study is the first to report the behavioural effects of ethanol in L. variegatus. Our results show that this is a model organism for use in ethanol studies, providing further evidence for its utility in pharmacological research. [Abstract copyright: © 2024 The Author(s). Genes, Brain and Behavior published by International Behavioural and Neural Genetics Society and John Wiley & Sons Ltd.]